2019
DOI: 10.1016/j.ebiom.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased proton-sensing receptor GPR4 signalling promotes colorectal cancer progression by activating the hippo pathway

Abstract: BackgroundColorectal cancer (CRC) is one of the high incidences tumours and is ranked second in cancer-related mortality. Even though great progress has been made, there are no effective therapeutic strategies for late stage and metastatic CRC patients. Acidity is one characteristic of the tumour microenvironment. However, how cancer cells respond to this acidic environment surrounding them remains largely unknown, especially in colorectal cancer.MethodsProton sensor receptor expression was analysed in GEO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…In the brains of patients with Alzheimer's disease, PNMT protein at the axon end is reduced due to reduced transport of PNMT [32]. Zhong M's research found that the proton-sensing receptor GPR4 is highly expressed in colorectal cancer (CRC) and promotes the metastasis of CRC cells by inhibiting LATS activity and YAP1 nuclear translocation [33]. Chen Z's research showed that DARPP-32 can further regulate the angiogenic effect of ANGPT2 by inducing STAT3 phosphorylation in gastric tumors [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the brains of patients with Alzheimer's disease, PNMT protein at the axon end is reduced due to reduced transport of PNMT [32]. Zhong M's research found that the proton-sensing receptor GPR4 is highly expressed in colorectal cancer (CRC) and promotes the metastasis of CRC cells by inhibiting LATS activity and YAP1 nuclear translocation [33]. Chen Z's research showed that DARPP-32 can further regulate the angiogenic effect of ANGPT2 by inducing STAT3 phosphorylation in gastric tumors [34].…”
Section: Discussionmentioning
confidence: 99%
“…GPR4 appeared up-regulated in cholangiocarcinoma, down-regulated in cervical and lung cancers, and increased or decreased in kidney tumors depending on the kind of cancer [150]. Analysis centered in particular cancers revealed the up-regulated expression of GPR4 in head and neck squamous cell carcinoma [151], in renal cell carcinoma [152], in colorectal cancer [153] and in hepatocellular carcinoma [154] and, in most of these studies, its high expression correlated with late stage tumors and poor overall survival [152][153][154][155].…”
Section: Gpr4mentioning
confidence: 98%
“…Functional studies show divergent roles of GPR4 in different types of cancer. On one hand, GPR4-knock out (KO) mice showed reduced tumorigenesis after the orthotropic transplantation of cells from murine breast (4T1) or colon cancer (CT26) cell lines [156] while suppression of GPR4 in human colorectal cancer (HCT116) cells significantly attenuated tumor growth of subcutaneous xenografts and reduced liver invasion in a metastasis model in nude mice [153]. This protumoral effect may be related with a proangiogenic activity since colonic tumors from GPR4-KO mice presented an altered vessel morphology, length and density [156] and GPR4-transfected cells promoted the formation of tubes by human microvascular endothelial cells in a paracrine manner in vitro [151].…”
Section: Gpr4mentioning
confidence: 99%
“…Recently, encouraging reports outlined the importance of the GPR4 gene itself in diseases, independent of SPC. GPR4 is also involved in the progression of head and neck cancer, epithelial ovarian cancer (EOC) and colorectal cancer [58,59]. A positive correlation between GPR4 expression and a higher microvascular density in EOC was observed, but this was not evident in benign ovarian tumor tissues [60].…”
Section: Occurrence and Mechanism Of Action Of Spcmentioning
confidence: 99%